Phylogenetic relationship of the Anguilliformes (Teleostei: Elopomorpha) with an emphasis in cephalic morphology - Espíndola, Vinícius Corrêa (2019)
Anguilliformes are a group of Teleostei fish with more than 1,000 species and 20 families. They were commonly known as eels, congers, and morays. The lack of consensus about the relationship hypotheses of a group in the last 40 years has mostly resulted from a lack of comprehensive studies bringing all families. Our study exposed the proposal for an integrated study of osteology and cephalic muscle and gill arches as a promising new source of characters to understand the intrarelationships of families which compound the order. With 108 terminal taxa, including representants of the 20 Anguilliformes families, the present study realized the most extensive morphological analysis ever made with the group, totalizing 248 phenotypic characters. The results generated a topology which the Anguilliformes order had strong support with 28 synapomorphies, indicating Protanguilla basal position been a sister group of remaining members of the order. One clade compound by long snout eels presented for the first time on the present study, which \"Saccopharyngoidei\" shared nine characteristics with Nemichthyidae. Synaphobranchidae grouped with \"Chlopsidae\" (not recovered as a monophyletic group), Myrocongridae and Muraenidae, a new arrangement with support of two synapomorphies non-ambiguous. The present work also clarified the homology problem, such as palatine absent in Anguilliformes, opercle sutured to hyomandibular, interopercle associated to levator operculi, adductor mandibulae segmentum facialis and adductor hyomandibulae (= elevator muscles) identified in Saccopharyngoidei. Moreover, we observed the presence of some structure, still present in the remaining representants, not only found in Protangilla, as pre-maxillae in Derichthys and gill rakers in Heterocongrinae. The results pointed out that muscles characters were an essential source in clarifying Anguilliformes relationships.